2019
DOI: 10.31744/einstein_journal/2019ao4609
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of safety, effectiveness and reproducibility of telemedicine for neurosurgical screening

Abstract: Objective: To ascertain the safety, effectiveness and reproducibility of screening potential neurosurgical patients by means of smartphones. Methods: This is a retrospective and multicentric study. Data were collected from the medical records of patients subjected to real emergency neurosurgical evaluations and compared with assessments by neurosurgeons using smartphones to determine the feasibility of identifying changes in cranial computed tomography scans, potentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
(32 reference statements)
0
4
0
Order By: Relevance
“… 11 Studies have reported that in patients with neurosurgical emergencies, such as ischemic stroke or intracranial hemorrhage, remote consultation with radiographic imaging and simple neurological examination can reduce unnecessary transfers and provide specialty access to surgical patients. 17 , 18 However, no study in the literature has outlined how to overcome this challenge for patients with elective cranial or spine pathologies. Relatable, but not neurosurgical-specific, attempts at evaluating the musculoskeletal examination have been reported in a limited number of studies in the physiatry literature.…”
Section: Discussionmentioning
confidence: 99%
“… 11 Studies have reported that in patients with neurosurgical emergencies, such as ischemic stroke or intracranial hemorrhage, remote consultation with radiographic imaging and simple neurological examination can reduce unnecessary transfers and provide specialty access to surgical patients. 17 , 18 However, no study in the literature has outlined how to overcome this challenge for patients with elective cranial or spine pathologies. Relatable, but not neurosurgical-specific, attempts at evaluating the musculoskeletal examination have been reported in a limited number of studies in the physiatry literature.…”
Section: Discussionmentioning
confidence: 99%
“…It is important that these complimentary uses of telemedicine, such as exchanging messages with patients and using mobile videos for epileptic attacks recognition 11,12 , be recognized as telemedicine procedures that are subject to regulation, so that they can be carried out with safety for patients and neurologists. Some previous Brazilian experiences with telemedicine have been published, including the Belo Horizonte-Telehealth (BH-Telehealth) Program 13 , teledermatology in primary care in São Paulo 14 , neurology teleinterconsultation in three capitals in Brazil 15 , the TelessaúdeRS-UFRGS 16 program for teleregulation of care 17 , neurosurgery emergency consultation 18 , teleophthalmology in primary care 19 , and medical support by teleconsultation in emergency departments 20 . Most of these initiatives have government support through public universities or hospitals that are members of the Institutional Development Support Program of the Unified Health System (PROADI-SUS).…”
Section: Discussionmentioning
confidence: 99%
“…16 Studies from countries such as Brazil and Albania have shown that telemedicine is an effective way to determine the severity of cases and the need for transfer in neurotrauma. 17,18 By triaging patients through a telehealth platform, access to specialty care in a remote or rural setting is increased, and costs are decreased by preventing unnecessary transfers that can be managed by nonneurosurgeons. 17,18 Although telehealth has recently become more pervasive, it was only after COVID-19 that our department transitioned from primarily in-person clinic visits to telehealth for a wide variety of outpatient visits.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 By triaging patients through a telehealth platform, access to specialty care in a remote or rural setting is increased, and costs are decreased by preventing unnecessary transfers that can be managed by nonneurosurgeons. 17,18 Although telehealth has recently become more pervasive, it was only after COVID-19 that our department transitioned from primarily in-person clinic visits to telehealth for a wide variety of outpatient visits. Most importantly, by cancelling nonessential in-person hospital encounters, our patients had less contact with others in the hospital from whom they might be exposed to COVID-19.…”
Section: Discussionmentioning
confidence: 99%